Impact De La Fiscalite Sur La Croissance Economique Du Maroc - Moustapha Hamzaoui; Nezha Bousselhami (European Scientific Journal, ESJ, 2017)
This paper examines how the taxation (tax revenue) affects the economic growth in Morocco relying to the endogenous growth model of Barro (1990). After recalculating a new series of public capital and private capital and based on simultaneous equations model, one production function type Cobb Douglas with 3 factors (public capital, private capital and employment) has been estimated with data covering the period 1980-2015. The idea is to measure the effect of taxation on economic growth through its impact on public capital. The results find that the relationship between the two variables is positive. The householders can finance the public capital by taxes. And the public capital improves the economic growth.